Pendekatan Supervisi Direktif dalam Pembinaan Guru di Madrasah - Kurniawan, Febriyan; Maunah, Binti (Darajat: Jurnal Pendidikan Agama Islam, 2022)
As a school principal there are various models and approaches to supervising education. One of them is the directive approach pattern aimed at teachers who are lacking in tasks, principles, and functions as an educator. The purpose of this writing is to review 1) What is the Definition of Supervision and Directive Approach, 2) What are the Principles of Educational Supervision, 3) Who are the Targets of the Directive Approach, 4) What are the Characteristics of the Directive Approach, and, 5) How is the Directive Approach Technique in Teacher Development. The method used is literature study or literature review and the stages of data collection include analysis, editing, and discovery of data results. Then after that draw conclusions according to the literature review found. The results of this writing can be concluded, namely 1) The perspective of a head with an approach directed problems 2) The principles of educational supervision that are used as guidelines and guidelines, 3) The target of the directive approach to teachers with low responsibility complexity, 4) The characteristics of the directive approach such as vertical relationship, 5) Supervisors who build on         teachers.